Realms, regions and lords: Ireland and Scotland in the later Middle Ages - Michael Brown (Anales de la Universidad de Alicante. Historia Medieval, 2016)
Studies of the polities of the British Isles in the later middle ages have tended to deal with the individual lands or to place the English kingdom at the centre of discussions. However, in terms of their size and internal character there are good reasons for considering the Scottish kingdom and the lordship of Ireland as models of political society. Beneath the significant differences of status, law and external relationships, around 1400 the two lands can be regarded as sharing common experiences of government and internal warfare. These are most apparent from a regional perspective. Both Ireland and Scotland operated as regionalised polities in which the interests of major aristocratic houses predominated. The importance of such houses was recognised both internally and by the royal government. By looking at parallel regions, Munster and north-east Scotland, it is possible to identify comparable features and long-term differences between these societies.